Kulawy starzec, pokorny kamieniarz i szpetni zakonnicy… czyli o spotkaniu Żeromskiego z bratem Albertem - Legutko, Grażyna (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The main concept of the article concerns Stefan Zeromski’s exchange of thought with the attitudes of Brother Albert, who became a prototype of a “lame old man” in Żeromski’s first part of the trilogy Struggle with Satan. The author concerns herself with the following issues: whether Żeromski ever personally Brother Albert and why The Conversion of Judas (Nawracanie Judasza) did not impress him. The article also explores issues related to what extent the attitudes of main hero of The Conversion of Judas are a consequence of Żeromski’s personal convictions or if the intriguing story of Adam Chmielowski’s (Brother Albert) life influenced the creation of the literary character’s personality.